Reconstruction Of The Thumb (Study of 100 Cases) - Dr. Ashok C. Shah; Dr. S. M. Mahaluxmivala (Indian Journal of Plastic Surgery)
We have evaluated 100 cases with particular emphasis on tip losses and total thumb loss. Various methods and follow up of partial thumb reconstruction and total thumb reconstruction are discussed.